Computational fluid dynamics modelling of the dairy drying processes - Jolius, Gimbun; Law, Woon Phui; Anandharamakrishnan, C. (Wiley-Blackwell, 2017)
Computer simulations of the drying of dairy products are now widely used in food engineering research.They enable the underlying mechanismand performance of the drying process to be predicted, which is useful for design retrofits to improve performance or to optimize the operation of existing equipment. Mathematical equations describing momentum, heat and mass transfer coupled with equilibrium and kinetic equations, which usually form a model for a drying operation, are often solved together. In this chapter, a brief description of the principles of computational fluid dynamics (CFD) for the solution of fluid flows with heat and mass transfer is outlined in the case of spray drying, spray freeze drying and freeze drying. CFD solutions are routinely used to optimize and develop drying equipment as evident in the significant increase in the number of peer-reviewed papers related to CFD applications to drying processes over the years (Figure 9.1). Figure 9.1 shows that the number of papers that specifically analyse freeze and spray-freezing operations using CFD is still relatively small. Current progress and best modelling practices are also reviewed. Finally, future direction and challenges in the modelling of dairy drying are presented.